Development and validation of an HPLC-DAD method for simultaneous quantification six ginsenosides in cultivated Panax vietnamensis var. fuscidiscus - Quyen, Duong Hong To; Hien, Nguyen Vo Thu; Huong, Nguyen Thu; Ngu, Vo Quoc; Oanh, Hua Hoang; Nam, Nguyen Phuong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Panax vietnamensis var. fuscidiscus K. Komatsu, S. Zhu & S.Q. Cai is a rare medicinal plant endemic to Vietnam, known for its rich profile of pharmacologically active ginsenosides. Objective: This study aimed to develop and validate a high-performance liquid chromatography method with diode array detection (HPLC-DAD) for the simultaneous quantification of six key ginsenosides: Ginsenoside Rg1, Majonoside R2, Ginsenoside Rb1, Notoginsenoside R4, Notoginsenoside Fc, and Ginsenoside Rd. Methods: Chromatographic separation was achieved using a Shim-pack GIST C18 column (250 × 4.6 mm, 5 μm) on a Shimadzu LC-2030C 3D Plus system. A gradient elution with water and acetonitrile was employed, and detection was performed at 195 nm. All six compounds were baseline-separated within 50 minutes (Rs > 1.5). The extraction process was optimized using ultrasound-assisted extraction with ethanol:water (1:1), a material-to-solvent ratio of 1/50, 20-minute extraction time, repeated twice. Results: The method demonstrated good specificity, linearity (R² > 0.999), and precision (RSD < 2.7%). Limits of detection ranged from 0.012% to 0.021%, and limits of quantification from 0.040% to 0.068%. Accuracy, confirmed by recovery tests, ranged from 97.08% to 102.89%. Conclusion: The developed HPLC-DAD method is accurate, precise, and reproducible, providing a reliable analytical tool for the quality assessment and standardization of Panax vietnamensis var. fuscidiscus K. Komatsu, S. Zhu & S.Q. Cai and its derived herbal products.